Les éléments culturels dans la bande dessinée « de Semarang à Nice : Voyage Interculturel Indonésien - Français » - Sri Maryati; Sri Handayani (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Culture can be a characteristic of each region where it originates, resulting in cultural differences between one region and another. Indonesia and France are countries that are rich in culture. This study aims to find and explain cultural elements in the form of ideas, activities, and artifacts in Indonesian and French cultures. The type of research used is descriptive-interpretive, which originates from a comic entitled "From Semarang to Nice: A Cross-Cultural Journey between Indonesia and France". The result of this study is the discovery of cultural elements in Indonesian and French culture in these comics based on the three forms of culture according to Koentjaraningrat. In the first form of culture, in the form of ideas, elements of knowledge, human way of life, habits, attitudes, ideas, regulations, language, norms, religion, and customs are found. In the second form of culture, in the form of activity, elements of knowledge, the human way of life, habits, customs, art, and religion are found. Then, in the last form of culture, in the form of artifacts, were found elements of knowledge, art, history, meaning, tools of life, and technology.